Improving Image Quality of Pancreatic Cancer and Surrounding Vessels with Spectral CT Imaging - Miao, Qi; Li, Xiaoling; Ren, Ke; Zhao, Yu; Zhao, Li; Xu, Ke (Current Medical Imaging, 2015)
MDCT is considered as the principle imaging modality utilized for evolution of suspected pancreatic cancer. But there is a subset of pancreatic cancer may be notable. Spectral CT can create monochromatic images which reduce beam-hardening artifacts, improve image quality and optimize lesion contrast. Methods: Thirty-one patients with pancreatic cancer underwent spectral CT to generate conventional 140kVp polychromatic images (group A) and monochromatic images, with energy level from 40 to 140 keV (group B) during arterial phase and portal venous phase. ANOVA compared the tumor-to-pancreas contrast-to-noise ratio (CNR), image noise, artery-totumor CNR. Readers’ subjective evaluations of image quality were recorded. Results: The lower image noise for group B was at 65-80keV during 40-80keV (p<0.05). Higher tumor-to pancreas CNR values of arterial phase and portal venous phase in group A and B were distributed at 55-65 keV (p<0.05). Artery-totumor CNR value was higher at 40-70 keV in group A and B (p<0.05). Higher image quality score were obtained at 55-65 keV than in group A and B (p<0.05). Compared with polychromatic images, tumor-to pancreas CNR values of arterial phase and portal venous phase, artery-to-tumor CNR of monochromatic images increased by 84.6%, 89.4% and 61.1%. Conclusions: The monochromatic imaging can improve image quality of pancreatic cancer and surrounding vessels by using single source dual-energy CT, and optimal energy level for display lesion, surrounding vessels were 40-65 keV and 40-70keV, respectively.
Keywords: Arteries